(untitled) (CIPEEX, 2025)
Introduction: Alopecia is a scalp disorder that directly affects the hair follicle, causing premature hair loss. However, combined treatment has a positive impact on reducing hair loss, and new hair growth is noticeable, since microneedling combined with minoxidil is an alternative treatment for this disorder. Objective: This study aims to highlight the effectiveness of combined therapeutic resources with cosmeceuticals for the treatment of alopecia. Method: This is a bibliographic research studied in academic sources such as Scielo and Google Scholar, using the keywords “hair microneedling,” “cosmeceuticals,” and “minoxidil,” obtaining 116 results, however, articles from 2018 to 2020 were filtered. In addition, the book Methods and Techniques of Aesthetic Evaluation, available in the virtual library, was consulted. Results: According to the studies analyzed, non-scarring alopecia conditions such as androgenetic alopecia (AGA), alopecia areata, and telogen effluvium are reversible, since the hair follicle has not yet died. In these cases, microneedling combined with the use of minoxidil showed positive results in increasing hair density. However, in cases of scarring alopecia, the condition becomes irreversible because inflammation causes permanent destruction and death of the follicle, making it impossible for new hairs to grow on the scalp. Conclusion: it can be concluded that combined technology for the treatment of scalp disorders, such as alopecia, has a positive impact on patients’ lives, given that hair is closely linked to human self-esteem.